STRUCTURE OF THE EDUCATIONAL PROCESS REGARDING SPORTS IN SEPARATE CLASSES - Abbasov Bakhadir Asatillayevich (Journal Park Publishing, 2024)
The theory of sports is a system of knowledge about the essence and structure of sports, about its most general laws, about the peculiarities of functioning in society, about the content and forms of optimal construction, preparation of an athlete to achieve high sports results. In this article highlights structure of the educational process regarding sports in separate classes.
Keywords: educational process, sport, sport theory, individual approach, construction, competitions, pedagogic skill.